Ryanodine receptor-active non-dioxin-like polychlorinated biphenyls cause neurobehavioral deficits in larval zebrafish - Yaghoobi, Bianca; Miller, Galen W.; Holland, Erika B.; Li, Xueshu; Harvey, Danielle; Li, Shuyang; Lehmler, Hans-Joachim; Pessah, Isaac N.; Lein, Pamela J. (Frontiers in Toxicology, 2022)
Although their production was banned in 1977, polychlorinated biphenyls (PCBs) continue to pose significant risks to the developing nervous system. Perinatal exposure to PCBs is associated with increased risk of neuropsychiatric disorders, perhaps due to altered patterns of dendritic arborization of central neurons. Non-dioxin-like (NDL) PCB congeners enhance dendritic arborization of developing mammalian neurons via sensitization of ryanodine receptors (RYR). Structure-activity relationships (SAR) of RYR sensitization by PCBs have been demonstrated using mammalian and rainbow trout (Oncorhynchus mykiss) tissue homogenates. The purpose of this study is to determine whether this SAR translates to developmental neurotoxicity (DNT) of PCBs in vivo, a question that has yet to be tested. To address this gap, we leveraged a zebrafish model to evaluate the DNT potential of PCBs 28, 66, 84, 95, 138, and 153, congeners previously shown to have broadly different potencies towards sensitizing RYR. We first confirmed that these PCB congeners exhibited differing potency in sensitizing RYR in zebrafish muscle ranging from negligible (PCB 66) to moderate (PCB 153) to high (PCB 95) RYR activity. Next, enzymatically dechorionated embryos were statically exposed to varying concentrations (0.1–10 M) of each PCB congener from 6 hours post-fertilization (hpf) to 5 days post-fertilization (dpf). Embryos were observed daily using stereomicroscopy to assess mortality and gross malformations and photomotor behavior was assessed in larval zebrafish at 3, 4, and 5 dpf. The body burden of each PCB was measured by gas chromatography (GC). The key findings are: (1) None of these PCBs caused death or overt teratology at the concentrations tested; (2) A subset of these PCB congeners altered photomotor behavior in larval zebrafish and the SAR for PCB behavioral effects mirrored the SAR for RYR sensitization; and (3) Quantification of PCB levels in larval zebrafish ruled out the possibility that congener-specific effects on behavior were due to differential uptake of PCB congeners. Collectively, the findings from this study provide in vivo evidence in support of the hypothesis that RYR sensitization contributes to the DNT of PCBs.